2012
DOI: 10.1007/s11356-012-1321-2
|View full text |Cite
|
Sign up to set email alerts
|

Multiple biomarkers of pollution effects in Solea solea fish on the Tunisia coastline

Abstract: This field study investigates the morphological indices (condition index, hepatosomatic index) and biochemical (catalase (CAT), glutathione S-transferase (GST), acetylcholinesterase (AChE), metallothionein (MT), lipid peroxidation) parameters in liver, gills and kidney of common sole (Solea solea) originating from different sites of the Tunisian coast area impacted by different anthropogenic activities. Differences among sites and tissues for AChE, GST, CAT, MT and TBARS were found and possibly related to know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 52 publications
4
8
0
Order By: Relevance
“…The susceptibility of the gills to pollutants, as described in the current study, means that there is a real risk of exposure for the local biota and an environmental health problem. Other studies have corroborated the same findings in the gills of other fish, including as Solea solea from the Tunisia coast (Jebali et al 2013), O. niloticus from heavily contaminated sites in Egyptian lakes (Abdel-Moneim et al 2012), and A. anguilla after exposure to metal-rich effluent from a bleached kraft pulp mill (Santos et al 2004). The increased LPO in the gills suggests that the gills have a less developed antioxidant mechanism compared to the liver and the kidneys.…”
Section: Discussionsupporting
confidence: 56%
“…The susceptibility of the gills to pollutants, as described in the current study, means that there is a real risk of exposure for the local biota and an environmental health problem. Other studies have corroborated the same findings in the gills of other fish, including as Solea solea from the Tunisia coast (Jebali et al 2013), O. niloticus from heavily contaminated sites in Egyptian lakes (Abdel-Moneim et al 2012), and A. anguilla after exposure to metal-rich effluent from a bleached kraft pulp mill (Santos et al 2004). The increased LPO in the gills suggests that the gills have a less developed antioxidant mechanism compared to the liver and the kidneys.…”
Section: Discussionsupporting
confidence: 56%
“…Although organophosphate and carbamate pesticides are the two main classes of compounds ascribed for AChE inhibition (Fulton and Key 2001), it has also been shown that other chemicals can interact with AChE activity, such as metals, detergents and PAHs (Lionetto et al 2013). Thus, low AChE activities are frequently found in mussels and fish at impacted sites in various regions under different types of pollution Jebali et al 2013;Bellas et al 2014) which is in agreement with the present study.…”
Section: Discussionsupporting
confidence: 92%
“…The enzyme response to pollutants shows a bell-shaped trend, with an initial increase in activity due to the activation of enzyme synthesis followed by a decrease in enzymatic activity, due to the enhanced catabolic rate and/or a direct inhibitory action of toxic chemicals on the enzyme molecules (Viarengo et al 2007). Thus, high CAT activities found in mussels and fish at polluted sites are considered an adaptive response to ROS-inducing contaminants (Roméo et al 2003;Cappello et al 2013;Jebali et al 2013) whereas low CAT activities at polluted sites are linked with increased susceptibility to oxidative stress (Regoli et al 2004;Pampanin et al 2005a;Oliva et al 2012). Accordingly, the low CAT activities observed in this 16 study in mussels collected from the impacted sites suggest oxidative stress experienced by these animals.…”
Section: Discussionmentioning
confidence: 63%
“…The choice of an adequate sentinel is also of utter importance, and the benthic fish sole, Solea solea, has been proved to be adequate as it fulfils the requirements of a good bioindicator and has a high economic interest. Field and laboratory studies have demonstrated its suitability as sentinel (Jebali et al 2013;Ribecco et al 2012;Siscar et al 2015).…”
Section: Introductionmentioning
confidence: 99%